1991
DOI: 10.1136/ard.50.12.915
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of the elastase inhibitory activity of alpha 1 antitrypsin in fresh samples of synovial fluid from patients with rheumatoid arthritis.

Abstract: The proteinase inhibitory ability of a, antitrypsin was measured in 23 samples of rheumatoid arthritis synovial fluid, eight osteoarthritic synovial fluids and nine normal control serum samples. For each sample a detailed kinetic analysis was performed with porcine pancreatic elastase as the target proteinase. Samples were stored for less than 24 hours at 4°C before analysis, which does not significantly alter the proportion of inactive a, antitrypsin. In rheumatoid synovial fluid the elastase inhibitory abili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
22
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(22 citation statements)
references
References 10 publications
0
22
0
Order By: Relevance
“…Okada et al demonstrated the proteolytic inactivation of TIMP-1 by neutrophil elastase [12] and suggested that neutrophils, which infiltrate inflammatory sites, may contribute to TIMP-1 inactivation. The lack of inhibitory capacity of the natural inhibitor of neutrophil elastase, ct-l-proteinase inhibitor, at inflammatory sites has been described [24].…”
Section: Discussionmentioning
confidence: 99%
“…Okada et al demonstrated the proteolytic inactivation of TIMP-1 by neutrophil elastase [12] and suggested that neutrophils, which infiltrate inflammatory sites, may contribute to TIMP-1 inactivation. The lack of inhibitory capacity of the natural inhibitor of neutrophil elastase, ct-l-proteinase inhibitor, at inflammatory sites has been described [24].…”
Section: Discussionmentioning
confidence: 99%
“…Oxidatively and proteolytically inactivated proteinase inhibitors have been detected in vivo in lung secretions from patients with cystic fibrosis [105,110], and in synovial fluid from patients with inflammatory arthritides [111][112][113][114]. Thus it is clear that, during infection and inflammation, oxidants and proteinases released from activated leukocytes and/or bacteria may act synergistically to create microenvironments in which extracellular proteolysis by leukocyte proteinases is facilitated via the inactivation of proteinase inhibitors.…”
Section: Inactivation Of Proteinase Inhibitorsmentioning
confidence: 99%
“…20,21 AT contains methionine at the "P1 position," which is located in the reactive site, and determines the specificity of inhibition. Various oxidant radicals such as peroxide, the hydroxyl radical, hypochloride, chloramine, and peroxynitrite 22,23 change the methionine into methionine sulfoxide, and such modified forms of AT lose the inhibitory activity against proteinases.…”
mentioning
confidence: 99%